An essential need: Banishing permanently strict liability from the customs infringement procedures - Varela, Andrés (2017)
This paper analyzes the strict liability system surviving in customs infringement procedures, the grounds for its existence or survival and its consequences. Also, the arguments against such system of liability attribution are examined. Thus, from such starting point, through a precise enumeration of statutory rebuttable presumptions whose intention can be presumed whenever it is difficult for Tax Authorities to prove such presumptions, I intend to find legal solutions to determine the grounds for its replacement without affecting the rights of the relevant individuals or legal entities when the customs infringements are decided.